Contrato de EPC (Engeneering, Procurement e Construction) e o padrão FIDIC - Gozzi, Elcio Fagundes Marques (2016)
This dissertation aims at analyze the Engineering, Procurement and Construction Agreement (EPC) and its use as standard form, as presented by the International Federation of Consulting Engineers (FIDIC). The work is divided in two parts. The first, to verify the adequacy of construction agreement (empreitada) rules to the EPC agreement and the possible need for specific ruling on this matter. Analyzes the legal framework of construction agreement (empreitada) stated on Brazilian Civil Code, drawing a parallel with the main characteristics and differences between construction agreement (empreitada) and the EPC from its legal and economic perspective of project finance. The second part analyzes the main characteristics of the FIDIC’s EPC standard form, known as Silver Book, and its application in Brazil considering the peculiarities of our legal system.